High-dose nandrolone decanoate induces oxidative stress and inflammation in retroperitoneal adipose tissue of male rats - Magalhães, Saulo Chaves (2020)
The non-therapeutic use of the androgenic anabolic steroid Nandrolone Decanoate is popular due to its effects on physical performance and body composition, especially for its lipolytic and anabolic effects associated. However, high doses of such drugs are often associated with a series of pathologies related to unbalanced redox homeostasis, which, in turn, can be linked to inflammation. The oxidative stress onset could deregulate the secretion of cytokines, evidencing a dysfunctional adipocyte. Thus, the aim of this study was to investigate the effect of supraphysiological doses of Nandrolone Decanoate on redox homeostasis of retroperitoneal fatpad of male rats and its relationship with cytokines-based inflammatory signaling. Hydrogen peroxide production was assessed in the retroperitoneal fat pad of adult male rats which received either 10 mg kg of Nandrolone Decanoate or only a vehicle. Also, catalase, superoxide dismutase and glutathione peroxidase activities were measured, together with total reduced thiols and protein carbonylation, as well as IL-1β, TNF-α, and IL-6 local levels. High doses of Nandrolone Decanoate caused an increase in the hydrogen peroxide production, together with lower activities of the antioxidant enzymes and lower levels of total reduced thiol. There were also higher protein carbonylation and greater levels of IL-1β, TNF-α, and IL-6 in the treated group compared to control group. Therefore, it was possible to verify that high doses of Nandrolone Decanoate cause oxidative stress and induce higher inflammatory signaling in retroperitoneal fat pad of male rats.